Dialogue as a Trans-disciplinary Concept Martin Buber's Philosophy of Dialogue and its Contemporary Reception - Mendes-Flohr, Paul (Studia Judaica, 2015)
This volume of essays takes as its point of departure Martin Buber`s principle of dialogue, which he applied as a comprehensive hermeneutic method for the study of various cultural phenomena. The volume critically evaluates the methodological purchase to be gained by the introduction of Buber`s conception of dialogue in political theory, psychology and psychiatry, and religious studies.